Gait motion for naturally curving variously shaped corners. (17th January 2018) - Akiyama, Yasuhiro; Okamoto, Shogo; Toda, Hitoshi; Ogura, Takao; Yamada, Yoji
Abstract: Modeling the curving motion of humans in actual environment is rarely done because of the complexity and variability of the turning motion. In this study, various gait motions, including straight, round corner, and circular walks, were recorded and analyzed using factor analysis. As a result, we successfully extracted several factors that represent turning motions, such as long stride motion, turning motion led by the inner leg, and turning motion led by the outer leg. In particular, we found that the natural curving motion, which is a motion that results when turning around a round corner, is widely and continuously distributed on the factor space. Although several typical stepping strategies were reported by related studies, we found that the stepping motion changes between straight and turning gaits in the factor space during natural curving motions. Thus, the classification of curving motion into several typical distinct stepping patterns is probably insufficient to understand the natural curving motion. Furthermore, natural curving motions that comprise circular curving motions that were believed to represent typical curving motions was not validated. On the other hand, this result also suggests the possibility of generating curving motions for a physical assistant robot by combining straight gait and circler curving motion. Graphical Abstract: